The EPPO/OLAF compendium of national procedures: Cyprus - Hauck, Pierre; Schneider, Jan-Martin; Justus Liebig University Giessen (My University, 2024)
This Cypriot EPPO/OLAF volume deals with the link between national law and EU law (EPPO and OLAF Regulations) and enables professionals from the justice sector to understand the national law in comparative perspective and to plan further investigations. It refers to fraud cases, the link between OLAF and AFCOS, and the activities of the new EPPO regional offices. The Cypriot Act for the Implementation of the EPPO and the rules for defence lawyers in EPPO cases involving tax, subsidy, and customs fraud are also discussed. Attorney Dr Marilena Katsogiannou's introductory chapter to the Compendium on Cyprus provides a thorough summary of both Union and Cypriot laws in relation to EU fraud offences. While this volume is written in English, its footnotes reproduce the original national legislation in the local language.
Keywords: ddc:340; ddc:320